Examining Critical Factors Affecting the Interaction of Farmers with Researchers in Agricultural Innovation in Ethiopia - Bayissa, Debella Deressa (American Journal of Human Ecology, 2015)
Ethiopia is the second most populated country having more than 90 million people in Africa. Ethiopian economy largely depends on agriculture. Low agricultural production has created national food insecurity. This was because of insufficient knowledge transfer between researchers and farmers. The interaction of researchers with farmers was weak. Therefore, it was inspiring to investigate critical factors hindering the interaction of researchers with farmers in agricultural innovation in Ethiopia. A qualitative research design was used. A snowball sampling technique was employed. The study revealed that resource limitations, ineffective extension system, weak coordination among different stakeholders and lack of strong attention for research from government critically hindered the interaction of researchers with farmers. The research affirmed that the number of researchers was not sufficient to conduct demand driven research. Besides inefficient use of resources, it was monopolized by a few elite researchers. The different actors working in agriculture had less readiness and willingness to learn from one another. Moreover, there was weak institutionalized body that coordinate the efforts of different stakeholders.